A National Assessment on Patient Safety Curricula in Undergraduate Medical Education: Results From the 2012 Clerkship Directors in Internal Medicine Survey. Issue 1 (March 2020) - Jain, C. Charles; Aiyer, Meenakshy K.; Murphy, Elizabeth; Alper, Eric A.; Durning, Steven; Aldag, Jean; Torre, Dario
Abstract : Objectives: Patient safety is a cornerstone of quality patient care, and educating medical students about patient safety is of growing importance. This investigation was a follow-up to a 2006 study to assess the current status of patient safety curricula within undergraduate medical education in North America with the additional goals of identifying areas for improvement and barriers to implementation. Methods: Thirteen items regarding patient safety were part of the 2012 Clerkship Directors in Internal Medicine annual survey. Questions addressed curriculum content, delivery, and barriers to implementation. Results: Ninety-nine clerkship directors (82%) responded. Forty-one (45.6%) reported that their medical school had a patient safety curriculum taught during medical school as compared with 25% in a 2006 survey. Fifteen (20%) reported satisfaction with students' level of safety competency at the end of the clerkship. Barriers to implementation included lack of faculty time (n = 57, 78.1%), lack of trained faculty (n = 47, 65.3%), and lack of a mandate from school's dean's office (n = 27, 38.0%). Conclusions: Our study found that less than half of North American medical schools have a formal patient safety curriculum; although this is higher than in 2006, it still exemplifies a major gap in undergraduate medical education.